Inclusion of gaming disorder in the diagnostic classifications and promotion of public health response: Commentary to the “Scholars’ open debate paper on the World Health Organization ICD-11 Gaming Disorder proposal”: A perspective from Iran - Shadloo, Behrang (J Behav Addict, 2017)
There are ongoing controversies regarding the upcoming ICD-11 concept of gaming disorder. Recently, Aarseth et al. have put this diagnostic entity into scrutiny. Although we, a group of Iranian researchers and clinicians, acknowledge some of Aarseth et al.’s concerns, believe that the inclusion of gaming disorder in the upcoming ICD-11 would facilitate necessary steps to raise public awareness, enhance development of proper diagnostic approaches and treatment interventions, and improve health and non-health policies.